Motion control systems - Sabanovic, Asif; Ohnishi, K. (Kouhei), 1952- (IEEE Press ; John Wiley & Sons (Asia) Pte Ltd, 2011)
"Presents a unified approach to the fundamental issues in motion control, starting from the basics and moving through single degree of freedom and multi-degree of freedom systems In Motion Control Systems, Šabanovic and Ohnishi present a unified approach to very diverse issues covered in motion control systems, offering know-how accumulated through work on very diverse problems into a comprehensive, integrated approach suitable for application in high demanding high-tech products. It covers material from single degree of freedom systems to complex multi-body non-redundant and redundant systems. The discussion of the main subject is based on original research results and will give treatment of the issues in motion control in the framework of the acceleration control method with disturbance rejection technique. This allows consistent unification of different issues in motion control ranging from simple trajectory tracking to topics related to haptics and bilateral control without and with delay in the measurement and control channels. Šabanovic and Ohnishi offer a gradual passage from the simplest single degree of freedom systems to most complicated task control in redundant multi-body systems. The salient properties of the control approach can be grasped in a full extent, and the control of multi-body systems becomes a natural extension of the single degree of freedom systems and can be easily followed. Goes beyond component level of most existing books and introduces systemic, fundamental issues with diverse application Offers graduated increase in complexity through the book, with reinforcement in subsequent chapters Explains the fundamentals through implementation examples, with illustrations in MATLAB/SIMULINK or with experimental results Gives newcomers solid grounding in modeling and control Based on classroom tested materials and the authors' original research work Written by the leading researchers in sliding mode control (SMC) and disturbance observer (DOB) Lecture notes on the companion website for instructors to download Simulink and MATLAB code for readers to download"--